THE IMPACT OF READING TECHNIQUES INCLUDING SKIMMING AND SCANNING ON STUDENTS' READING COMPREHENSION (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article investigates the effectiveness of the scanning reading strategy among higher education students in enhancing reading comprehension. The study employs a mixed-methods approach, incorporating quantitative and qualitative data analysis. The results reveal the impact of scanning on reading comprehension and suggest implications for educators and learners.